Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Given that [tex]\(\tan(x) = \frac{7}{2}\)[/tex] and [tex]\(180^\circ \leq x \leq 270^\circ\)[/tex], which means [tex]\(x\)[/tex] is in the third quadrant where both sine and cosine are negative.
We start by using the identity of tangent:
[tex]\[ \tan(x) = \frac{\sin(x)}{\cos(x)} = \frac{7}{2} \][/tex]
In the third quadrant, both [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex] are negative. We can represent [tex]\(\sin(x)\)[/tex] as [tex]\(-7k\)[/tex] and [tex]\(\cos(x)\)[/tex] as [tex]\(-2k\)[/tex] for some positive constant [tex]\(k\)[/tex].
By using the Pythagorean identity:
[tex]\[ \sin^2(x) + \cos^2(x) = 1 \][/tex]
Substituting [tex]\(\sin(x) = -7k\)[/tex] and [tex]\(\cos(x) = -2k\)[/tex] into the identity:
[tex]\[ (-7k)^2 + (-2k)^2 = 1 \][/tex]
[tex]\[ 49k^2 + 4k^2 = 1 \][/tex]
[tex]\[ 53k^2 = 1 \][/tex]
Solving for [tex]\(k\)[/tex]:
[tex]\[ k^2 = \frac{1}{53} \][/tex]
[tex]\[ k = \frac{1}{\sqrt{53}} \][/tex]
Now, substituting [tex]\(k\)[/tex] back into [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex]:
[tex]\[ \sin(x) = -7k = -\frac{7}{\sqrt{53}} \][/tex]
[tex]\[ \cos(x) = -2k = -\frac{2}{\sqrt{53}} \][/tex]
The double angle formula for sine is:
[tex]\[ \sin(2x) = 2 \sin(x) \cos(x) \][/tex]
Substituting [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex] into this formula:
[tex]\[ \sin(2x) = 2 \left(-\frac{7}{\sqrt{53}}\right) \left(-\frac{2}{\sqrt{53}}\right) \][/tex]
[tex]\[ \sin(2x) = 2 \cdot \frac{14}{53} \][/tex]
[tex]\[ \sin(2x) = \frac{28}{53} \][/tex]
So, the value of [tex]\(\sin(2x)\)[/tex] is:
[tex]\[ \boxed{\frac{28}{53}} \][/tex]
We start by using the identity of tangent:
[tex]\[ \tan(x) = \frac{\sin(x)}{\cos(x)} = \frac{7}{2} \][/tex]
In the third quadrant, both [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex] are negative. We can represent [tex]\(\sin(x)\)[/tex] as [tex]\(-7k\)[/tex] and [tex]\(\cos(x)\)[/tex] as [tex]\(-2k\)[/tex] for some positive constant [tex]\(k\)[/tex].
By using the Pythagorean identity:
[tex]\[ \sin^2(x) + \cos^2(x) = 1 \][/tex]
Substituting [tex]\(\sin(x) = -7k\)[/tex] and [tex]\(\cos(x) = -2k\)[/tex] into the identity:
[tex]\[ (-7k)^2 + (-2k)^2 = 1 \][/tex]
[tex]\[ 49k^2 + 4k^2 = 1 \][/tex]
[tex]\[ 53k^2 = 1 \][/tex]
Solving for [tex]\(k\)[/tex]:
[tex]\[ k^2 = \frac{1}{53} \][/tex]
[tex]\[ k = \frac{1}{\sqrt{53}} \][/tex]
Now, substituting [tex]\(k\)[/tex] back into [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex]:
[tex]\[ \sin(x) = -7k = -\frac{7}{\sqrt{53}} \][/tex]
[tex]\[ \cos(x) = -2k = -\frac{2}{\sqrt{53}} \][/tex]
The double angle formula for sine is:
[tex]\[ \sin(2x) = 2 \sin(x) \cos(x) \][/tex]
Substituting [tex]\(\sin(x)\)[/tex] and [tex]\(\cos(x)\)[/tex] into this formula:
[tex]\[ \sin(2x) = 2 \left(-\frac{7}{\sqrt{53}}\right) \left(-\frac{2}{\sqrt{53}}\right) \][/tex]
[tex]\[ \sin(2x) = 2 \cdot \frac{14}{53} \][/tex]
[tex]\[ \sin(2x) = \frac{28}{53} \][/tex]
So, the value of [tex]\(\sin(2x)\)[/tex] is:
[tex]\[ \boxed{\frac{28}{53}} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.